Circumnuclear Structures in Megamaser Host Galaxies - Pjanka P; Greene JE; Seth AC; Braatz JA; Henkel C; Lo FKY; Lasker R (IOP PUBLISHING LTD, 2025)
Using the Hubble Space Telescope, we identify circumnuclear (100-500 pc scale) structures in nine new H2O megamaser host galaxies to understand the flow of matter from kpc-scale galactic structures down to the supermassive black holes (SMBHs) at galactic centers. We double the sample analyzed in a similar way by Greene et al. and consider the properties of the combined sample of 18 sources. We find that disk-like structure is virtually ubiquitous when we can resolve <200 pc scales, in support of the notion that non-axisymmetries on these scales are a necessary condition for SMBH fueling. We perform an analysis of the orientation of our identified nuclear regions and compare it with the orientation of megamaser disks and the kpc-scale disks of the hosts. We find marginal evidence that the disk-like nuclear structures show increasing misalignment from the kpc-scale host galaxy disk as the scale of the structure decreases. In turn, we find that the orientation of both the similar to 100 pc scale nuclear structures and their host galaxy large-scale disks is consistent with random with respect to the orientation of their respective megamaser disks.